Analysis of quality and microstructure of freshly potato strips fried with different oils. (November 2020) - Li, Peiyan; Wu, Gangcheng; Yang, Dan; Zhang, Hui; Qi, Xiguang; Jin, Qingzhe; Wang, Xingguo
Abstract: The quality of French fries is a key factor which affect consumer's willingness to buy it. During this study, the effects of ten commercial edible oils on the content and status of water and oil, color, texture, volumetric shrinkage and microstructure of freshly fried fries were investigated. Fries fried in rice bran oil had higher water content, volumetric shrinkage, hardness, luminosity and yellowness, as well as lower oil content and redness than those fried in other oils. Lower transverse relaxation time was observed in fries fried with high-oleic sunflower oil. Scanning electron microscopy revealed a severely damaged internal structure. Magnetic resonance imaging visualized a thicker crust in freshly fried fries. Sensory results indicated that the fries fried in rice bran oil had a superior mouthfeel and a lower oil content compared to those fried with other oils. This work can provide a useful reference for the consumers to choose appropriate oil when preparing the fries. Highlights: Fatty acid composition of ten edible oils was determined. The water mobility of fries fried in different oils varies. Core and crust regions of fries was observed by magnetic resonance imaging. Severe distortion inside the fries was revealed by scanning electron microscopy. The fries fried in rice bran oil had better quality than fried in other oils.